O momento da tributação dos lucros auferidos por coligadas e controladas no exterior - Miranda, Fabiana Francisco de (2015)
Due to the phenomenon of globalization, the principle of territoriality has been replaced by the principle of universality worldwide income taxation , now considering taxable income earned by companies based in Brazil, regardless of where the income is produced. After several legislative changes and court decisions about the worldwide taxation of income tax, the Law n. 12.973/2014 brought a new system of accounting and taxation of income tax of foreigner subsidiary companies. In this context, it is essential the study of the concepts of economic and legal availability, in order to ascertain whether in this case there is the possibility of income tax and social contribution incidence or if this occurs only during the actual distribution of the profits